Survey of Antibiotic Use for Treating Community-acquired Pneumonia in Children at Vinh Medical University Hospital in 2022-2023 - Dien Minh, Nguyen; Thi Cam Nhung, Nguyen; Cuc, Hoang Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 1DO - 10.25073/2588-1132/vnumps.4688, 2025)
The study aimed to investigate the use of antibiotics for treating community-acquired pneumonia (CAP) in children at Vinh Medical University Hospital in 2022-2023. Materials and Methods: A cross-sectional descriptive study was conducted on 186 children aged 2 months to 5 years diagnosed with CAP. Results and Discussions: The male/ female ratio was 57.5%/ 42.5%. The age group of 12 to 48 months had the highest incidence of CAP, accounting for 58.1%. Children with CAP exhibited symptoms such as cough, difficulty breathing, wheezing, and chest wall retractions. White blood cell (WBC) counts and C-reactive protein (CRP) levels were typically elevated, along with the presence of lesions on chest X-rays. The rates of children with pneumonia and severe pneumonia were 73.7% and 26.3%, respectively. Several cases were associated with respiratory tract infections. A significant proportion of children used antibiotics before hospitalization. The most used treatment regimen was a combination of penicillin plus a beta-lactamase inhibitor, and a macrolide. The rate of regimen change was high, attributed to the improvement of clinical symptoms. The average treatment duration for pneumonia was 7.09 days, with a treatment success of 78.5%. Conclusion: Younger children had higher rates of CAP, and the antibiotic combination regimen of penicillin plus a beta-lactamase inhibitor and a macrolide was the most frequently used, showing high effectiveness in curing the infection with a ratio of 78.5%.